1981
DOI: 10.2134/jeq1981.00472425001000020002x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Physical Properties Due to Organic Waste Applications: A Review

Abstract: Land application of organic wastes such as animal manure, municipal wastes, and sewage sludge could alter the soil physical properties. Repeated substantial applications of waste increase the soil organic matter percentage. The available data on effects of waste applications on soil physical properties such as bulk density, water holding capacity at both field capacity and wilting point, and saturated hydraulic conductivity were summarized. Based on data from 12 different sources, 21 soil types, 7 waste types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
201
1
24

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(248 citation statements)
references
References 0 publications
22
201
1
24
Order By: Relevance
“…The increase in soil moisture (%) can be attributed to the improvement in soil structure and water holding capacity of the soil due to addition of organic manures. These results are in line with the findings of Gupta et al, (1977), Khaleel et al, (1981), Metzger and Yaron (1987). Bijalwan (2010) reported that soil moisture was higher in agri-horticulture compared to sole agriculture (tree less or control).…”
Section: Available Potassiumsupporting
confidence: 88%
“…The increase in soil moisture (%) can be attributed to the improvement in soil structure and water holding capacity of the soil due to addition of organic manures. These results are in line with the findings of Gupta et al, (1977), Khaleel et al, (1981), Metzger and Yaron (1987). Bijalwan (2010) reported that soil moisture was higher in agri-horticulture compared to sole agriculture (tree less or control).…”
Section: Available Potassiumsupporting
confidence: 88%
“…However, the relatively rapid rates of in®ltration could represent a potential for leaching losses to groundwater. Effects of sludge application on ®eld water-holding capacity were insigni®cant (Table 5) and expected to be minimal in ®ne-textured soils (Khaleel et al, 1981). The higher bulk density of the sludge row and inter-row areas is attributed to soil compaction as a result of increased traf®c of the sludge injection operation.…”
Section: Resultsmentioning
confidence: 99%
“…OM improves the physical, chemical and biological properties of soil, as well as giving a better soil aggregation, available water content and enhanced cation exchange capacity, leading to improved soil fertility (Khaleel et al, 1981;Metzger and Yaron, 1987;Matsumoto et al, 1999;Farooq and Nawaz, 2014). The addition of FCW also increased the soil N, P and K content, which showed a high correlation with the measured plant yield components.…”
Section: Discussionmentioning
confidence: 87%